Systematic Review of Green Seaweed Caulerpa racemosa as an Anti-Inflammatory Agent: Current Insights and Future Perspectives - Prayogo, Ega Widya; Irawati Sholikhah; Suciati; Dej-adisai, Sukanya; Retno Widyowati (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2024)
Background: Seaweed is a marine biota with many benefits, one of which is C. racemosa. It is one type of seaweed that is quite widely found in Indonesia. Objective This study investigated the anti-inflammatory activity of C. racemosa using various in vitro and in vivo approaches. Methods: A literature review was conducted by searching for research data on C. racemosa. The literature was obtained from PUBMED, ScienceDirect, Scopus, SpringerLink, and Google Scholar using the keywords C. racemosa, sea grapes, in vivo, in vitro, and anti-inflammatory. The search identified 1313 articles with 100 articles in Scopus, 100 articles in ScienceDirect, 0 articles in PubMed, 3 articles in SpringerLink, and 1,110 articles in Google Scholar. Results: The study showed 12 articles found C. racemosa has the ability as an anti-inflammatory both with in vitro and in vivo study approaches and supported by data on proximate composition which is quite high and substance consisting of various bioactive constituents including flavonoids, phenolics, phytosterols, terpenoids, saponins and alkaloids where the anti-inflammatory active isolate caulerpin was successfully isolated. C. racemosa is able to reduce the inflammatory response by inhibiting NO production and the release of cytokines and inflammatory mediators such as AMPK, mTOR, TNF-α and IL4. Conclusion: C. racemosa indicated that this species is a rich source of phytochemicals with many pharmacological activities, one of which is anti-inflammatory. Further research is required to explore the relationship between secondary metabolites and their activities.